"No first use" in the context of the U.S.-Japan Alliance. Issue 3 (2nd September 2022) - Akiyama, Nobumasa
Abstract: No first use (NFU) of nuclear weapons is said to be an effective declaratory policy for advancing nuclear disarmament. In Japan, which suffered two atomic bombings, there are many voices that expect the US to declare the NFU, hoping to promote nuclear disarmament. In the meantime, Japan faces a tough security environment with North Korea's growing nuclear and missile capabilities and, above all, China's more assertive actions along with the expansion of both nuclear and conventional forces. The Japanese strategic community thinks that it is essential to maintain the credibility of the US extended deterrence and to further develop strike capabilities to counter China's medium-range strike capabilities in the region. In this context, there is a concern that a possible US declaration of NFU, while it may reduce the nuclear risk between the US and China, may signal to China that the US would allow China's assertive activities at the regional level. Measures must be taken to dispel concerns about such regional instability, and stakeholders should pursue stability at both strategic and regional levels so that declaratory policies such as NFU can effectively contribute to reducing nuclear threats and risks. To this end, it would be beneficial to discuss arms control and build confidence through a multi-layered strategic and arms control dialogues among primary players, namely one between the US and China, one among the US, Japan, and China, and another that add other regional players.